The Leadership Management in Improving The Character - Lis M. Yapanto (Research Parks Publishers, 2021)
The role of a leader in an organization is very important because the existence of the leader is to become a doorstop or become one of the spearheads of success in organization. The role of a leader is inseparable from the implementation of management functions in the organization, starting from the planning organization including budgeting, organizing, staffing, actuating or leadership, coordinating and controlling or evaluating. However, every operational journey an organization will encounter obstacles or problems due to the dynamics of the organization's internal and external environment. To get around these situations and conditions, we need the art of intelligent leadership to achieve leadership effectiveness